Brucellosis is a public health problem in southern Italy: Burden and epidemiological trend of human and animal disease. Issue 6 (November 2018) - Facciolà, Alessio; Palamara, Maria A.R.; D'Andrea, Giuseppa; Marano, Fernanda; Magliarditi, Domenico; Puglisi, Giovanni; Picerno, Isa; Di Pietro, Angela; Visalli, Giuseppa
Abstract: Background: Brucellosis is the most common global bacterial zoonotic disease. Italian annual 2015 report on animal brucellosis control that was submitted to the Integrated National Plan of the Italian Health Ministry showed that the Italian region with the highest prevalence and incidence of brucellosis was Sicily (3.3%). This study aims to demonstrate the burden of disease and the epidemiological trend of human and animal brucellosis in Messina, Sicily, from 1997 to 2016. Methods: The analysis was conducted in the twenty-years 1997–2016. We examined the computerised and paper registers of the Messina Provincial Health Agency n.5 to evaluate human and animal brucellosis reports. Results: 1462 cases of human brucellosis were reported with an important outbreak in 2016 in which were reported 137 cases while the prevalence of infected cattle and sheep/goats decreased from 3.8% and 8%, respectively, in 1997 to 1.7% for both in 2016. A statistically significant correlation was observed between the decrease of both animal and human cases during the considered period. Conclusions: Our study demonstrate that brucellosis is still present in Sicily with a number of cases identified in both animals and humans and it hypothesises a large number of probable underreported cases. Our findings confirm the need to improve knowledge of the risks associated with consuming raw milk and its derivatives, mainly from sheep and goats, and demonstrates that public health would benefit from cooperation between human and veterinary health services.